As transformações econômicas e culturais nas cidades de fronteira Santo Antônio do Sudoeste - Brasil e San Antonio - Argentina - Campos, Elisandra Aparecida de (2014)
In this research we studied the transformations influenced the bordering the economy and culture of the cities of Santo Antonio do Sudoeste Brazil and San Antonio Argentina. These transformations have proved throughout the historical process of the cities to the present day, influencing the locals and the directions of local businesses in their customs, their economy, the efforts and financial investments in the border area. The main objective is to understand how these changes occurred, as this border territory is organized and how the border is seen by those who live or use the same in the cities studied.